The Inculturated Theology of Child Adoption among the Dayak Desa of West Kalimantan: An Anthropological Theology Model of Stephen Bevans - Dismas Kwirinus; Emanuel Martasudjita; Ignatius Dendi (International Journal of Social Service and Research, 2025)
This article examines the child-adoption practice within the Dayak Desa community of West Kalimantan through the lens of Inculturation Theology, employing Stephen Bevans’ anthropological model. The study explores symbolic dynamics, relational structures, and customary rituals as theological loci that illuminate a creative dialogue between Christian faith and local culture. Using a qualitative approach, it identifies values of inclusivity, kinship, and identity transformation embedded in the practice. The findings indicate that inculturation enables contextually meaningful theological reinterpretation while sustaining cultural traditions. This study contributes to the development of culturally sensitive contextual theology and promotes inter-tradition dialogue and inclusive expressions of faith.